New Australian hygrobatids (Acari: Hydrachnidia: Hygrobatidae), with the description of two new genera and three new species - Smit, Harry (Zootaxa, 2009)
Two new genera of the water mite family Hygrobatidae (Acari: Hydrachnidia) are described from Australia, Ioannibates gen. nov. and Pseudoaustraliobates gen. nov.. In addition, three new species are described, Ioannibates papillosus sp. nov., Pseudoaustraliobates flindersi sp. nov. and the second species of the genus Declinobates K.O. Viets, D. tasmanicus.